ANALYSIS OF BTCLS SKILL ASSESSMENT DIPLOMA NURSING (DIII) STUDENTS AT BINA SEHAT PPNI UNIVERSITY MOJOKERTO - Haryanto, Agus; So'emah, Eka Nur (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
DIII Nursing Study Programme students as prospective nurses must have good knowledge and skills in performing Basic Trauma Cardiac Life Support (BTCLS) actions, this is very important because BTCLS actions are carried out to help victims with cardiac arrest both at the hospital and outside the hospital. This study aims to determine the description of the evaluation of the value of knowledge and skills of BTCLS by students when attending training and post-training duration. The research method used was descriptive. Instruments with questionnaires to assess knowledge and observation sheets to see the value of skills. The sample in this study consisted of 58 respondents who were taken in each batch, namely batches 2021, 2022 and 2023. The results of this study were obtained from the evaluation of the value of BTCLS knowledge and skills which increased after training.The existence of a significant effect on the difference in treatment given to each variable is indicated by a sign ificance value of 0.042 < 0.005 in the 2021 results, and a significant value of 0.000 < 0.005 in 2022, while in 2023 the significant results show 0.000 < 0.005. Based on the results it can be concluded that there is an increase in knowledge and BLS skills. This study shows that the BTCLS training that has been carried out affective has a significant impact on participants.